Auditory verbal hallucinations in schizophrenia and post-traumatic stress disorder: common phenomenology, common cause, common interventions? - McCarthy-Jones, Simon; Longden, Eleanor (Frontiers in Psychology, 2015)
Auditory verbal hallucinations (AVH: ‘hearing voices’) are found in both schizophrenia and post-traumatic stress disorder (PTSD). In this paper we first demonstrate that AVH in these two diagnoses share a qualitatively similar phenomenology. We then show that the presence of AVH in schizophrenia is often associated with earlier exposure to traumatic/emotionally overwhelming events, as it is by definition in PTSD. We next argue that the content of AVH relates to earlier traumatic events in a similar way in both PTSD and schizophrenia, most commonly having direct or indirect thematic links to emotionally overwhelming events, rather than being direct re-experiencing. We then propose, following cognitive models of PTSD, that the reconstructive nature of memory may be able to account for the nature of these associations between trauma and AVH content, as may threat-hypervigilance and the individual’s personal goals. We conclude that a notable subset of people diagnosed with schizophrenia with AVH are having phenomenologically and aetiologically identical experiences to PTSD patients who hear voices. As such we propose that the iron curtain between AVH in PTSD (often termed ‘dissociative AVH’) and AVH in schizophrenia (so-called ‘psychotic AVH’) needs to be torn down, as these are often the same experience. One implication of this is that these trauma-related AVH require a common trans-diagnostic treatment strategy. Whilst antipsychotics are already increasingly being used to treat AVH in PTSD, we argue for the centrality of trauma-based interventions for trauma-based AVH in both PTSD and in people diagnosed with schizophrenia.